PECULIARITIES OF THE FORMATION AND DEVELOPMENT OF SOCIAL MATURITY IN FUTURE SPECIALISTS OF THE SOCIOECONOMIC PROFILE - SOROKA, Olha; PETRYSHYN, Liudmyla (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2024)
Abstract. The article describes the peculiarities of the formation and development of social maturity in future specialists of the socioeconomic profile, which include specialists in social work, social educators, psychologists, and medical professionals. The purpose of the study is specified in the tasks aimed at analysing research related to the disclosure of the content of the concept of "social maturity of the individual"; identifying the components of social maturity of students; presenting the stages of formation and development of social maturity in future specialists in socio-economic professions in the educational process of educational institutions of different accreditation levels. It has been established that social maturity is an integrative quality of a personality, in which the components are social activity, tolerance, orientation to spiritual values, reflection, creativity, and social responsibility. It is emphasized that the level of social status can be an integral criterion of the social maturity of an individual. Attention is focused on the period of studenthood (18–23 years) as the most favourable for young people to achieve a high level of social maturity, since during this period self-determination is based on stable interests and aspirations, is based on the worldview and is associated with the choice of future profession. The specificity of the formation and development of social maturity of future socio-economic specialists in institutions of professional higher education and HEIs provides for a phased, consistent, and possible involvement of students in various activities during and after school hours. The motivational, social-action, and social-creative stages of the formation of this phenomenon in students of educational institutions of different accreditation levels are distinguished. The motivational stage involves the formation of students' orientation of motivation for social and value-based activities. It is proposed to use the educational reserves of various academic disciplines (Time Management, Training Technologies, Theoretical and Applied Principles of Management). The socio-action stage provides students with skills to carry out social and value-based activities based on their own experience. The socio-creative stage is aimed at expanding the boundaries of social interaction and providing a wide range of opportunities for social interaction at different levels. It is proposed to use discussions, role-playing games, exercises, acting training, analysis of problem situations, etc. as organizational forms and teaching methods.